Spatial and temporal differences in the composition and structure of bacterial assemblages in biofilms of a rotating algal-bacterial contactor system treating high-strength anaerobic digester filtrate. (June 2020) - Johnson, Daniel B.; Schideman, Lance C.; Canam, Thomas; Hosen, Jacob D.; Hudson, Robert J.M.
Abstract: The microbial assemblages in biofilms growing on rotating algal-bacterial contactors (RACs) used to treat high-strength anaerobic digester filtrate were characterized during a 4-month study. Typical RAC-based systems supplied with feedstocks containing high total ammonia and comparatively low dissolved inorganic carbon ratios are nitrite-accumulating. The RACs have biofilms on their sunlit exterior surfaces (2 m 2 ) colonized by a mixture of phototrophs, chemoautotrophs, and heterotrophs, while the dark, internal media surface area (5 m 2 ) is colonized by chemoautotrophic and heterotrophic bacteria. We assayed the relative abundance of bacterial V4 16S segments in the RAC biofilms from November through February detecting the most significant differences in composition between interior and exterior biofilm surfaces and over time. Ten operational taxonomic units accounted for over 69% of the total individuals counted. Nitrosomonas, the common ammonia-oxidizing bacterial genus, was the 10th most abundant OTU and although ubiquitous it was more abundant on the dark, inside surfaces of the RACs. Highlights: Bacterial relative abundance varies spatially within the RAC system. Bacterial relative abundance varies over time in the RAC system. Bacterial co-occurrence differs between RAC biofilm surfaces. Ammonia oxidizing bacteria are more prevalent in internal biofilms. Ammonia oxidizing bacteria co-occur with denitrifying bacteria.